Effectiveness of zakat-based programs on poverty alleviation and economic empowerment of poor women: A case study of Bangladesh - Muhammad Anis, Fahami; Kassim, Salina (Islamic Economic and Finance Department, Bank Indonesia, 2016)
Bangladesh has long been suffering from poverty and its accompanying problems. During the past few decades, many initiatives have been implemented such as microcredit and cash transfer programs, yet the results seemed to be ambiguous. New frontiers are now sought to find new sources of finance which could offer a more effective and sustainable solution to the root cause of the poverty problem. Considering the idea of entrepreneurship and group-based development approach of microcredit, a zakat-based development approach was initiated in Bangladesh at a private level by an organization called Center for Zakat Management (CZM) for poverty alleviation and sustainable economic empowerment targeting poor women in rural areas. This paper aims to assess the effectiveness of the CZM efforts in utilizing zakat funds for promoting entrepreneurship among poor rural women. Focusing on the case of Bangladesh, this study assesses the effectiveness of zakat on aspects such as income, house hold expense and fixed asset accumulation of the poor client based on the “before and after” approach.